Ambulanta za bolezni odvisnosti Nova Gorica - Ščuka, Viljem (Zdravniški vestnik, 2001)
The author represents the Centre of prevention and treatment of an illegal drugs' addictions in Nova Gorica on the basis of analysis of the activities ofthe Centre in a first half-year of 2001. In that period the Centre treated 257 patients, among them 211 patients were addicted to heroin and just 68 of them (32%) were treated by methadone. The basic starting-point of the activities is an ambulant detoxification and participation of the patients andtheir relatives in the drugfree programmes, which are organised as an individual or group psychotherapyfora maintenance of the abstinence and personal development. In the last two years 110 patients were detoxificated from heroin, among them 22 are treated now for reappearance. There are 88 patients and 60 relatives (which is 42% of all treated by heroin addiction) included in the drug free programmes. The programme was medicamently supportedby naltrexon prophylaxis and sometimes by antidepresives for the period between half to one year. The author tries to introduce the successfulness of ambulant treatment of addictions under the condition of participation of clinical and psychotherapeutic approach and multidisciplinarity. He promotes the high-threshold programmes and criticises the lax and low-threshold use of methadone in the area of Northern Primorska region.
Keywords: (RS)-methadones; ambulante; bolezni odvisnosti; Heroin dependence; Heroin, zasvojenost; Ilegalne droge; javno zdravstvo; Metadon; Methadone; Nova Gorica; Snov, zloraba, centri za zdravljenje; Street drugs; Substance abuse treatment centers; Therapy